A cross-national analysis of bank selection decision and implications for positioning - Abou Aish, Ehab M. (2001)
This research attempts to increase the academic understanding as well as the managerial practices of the financial services marketing positioning in the crossnational field. In order to achieve this objective the research developed a conceptual framework of the small business' bank selection criteria and tested it on the small business banks' customers in two culturally different countries (Egypt and UK). This proposed framework was developed based on deduction, derived from the literature on positioning, branding and selection criteria, and induction, derived from two waves of exploratory pilot interviews in both countries. The research is divided into three main parts. The first part introduces the literature review, where the issues of positioning, branding and bank selection criteria were emphasised, ending with developing the proposed framework for small business' bank selection criteria. The second part deals with the empirical study, where the research design was explained and justified, the research hypotheses were developed, a multiface comparison between Egypt and the UK was presented, and finally the methodology adapted in this research was explained. This depends on the "mixed methods approach, dominant-less dominant design", i.e. depending on the qualitative methodology (in-depth interviews) in developing the "derived Etics view" as well as the research hypotheses, while the main part of the research is depending on quantitative methodology (sample survey based on structured questionnaire in both countries). The third part presents the data analysis in three chapters, while the first one deals with the descriptive and methodological issues, the second and third present the findings and the hypotheses testing results. The main results of this research emphasis that the bank selection decision could be better understood by the suggested conceptual framework. There are a lot of interfaces between the segmentation, positioning, branding, service quality, interactions, pre- and post purchase criteria, and a lot of integrated work is needed in order to gain a competitive advantage. Finally in general similar marketing positioning strategies could be adopted in the two studied countries on the banks' small business customers, as similar clusters of small business customers were identified. The adopted positioning strategy needs some minor adaptations in each country in order to get the desired objectives and work more effectively.